Efeito das técnicas de fusão sobre a fluidez de ligas do sistema cobre-alumínio. - Scaranelo, R. M.; Bombonatti, P. E.; de Barros, L. E.; Pellizzer, A. J. (My University, 1990)
It was evaluated the castability of four copper-aluminium alloy according the melting casting method used. The specimens were made using polyester mesh screen, with 11 x 11 filaments of 0.26 mm thick, fixed along of two adjacent edges in wax bar, with the sprue attached at their junction. The alloys were in an electrical casting machine and a centrifugal casting machine with an air/gas torch. The castability values were obtained by the percentage of completed segments of the resulting cast alloy screen. It was verified that the use of the electrical casting machine produced higher castability values to the copper-aluminium alloys than those produced by a centrifugal casting machine with an air/gas torch.
Effect of casting techniques on castability of copper-aluminum alloys
Keywords: aluminum; copper; dental alloy; denture; Aluminum; Copper; Dental Alloys; Dental Casting Technique; English Abstract